The acceptability and effectiveness of eHealth interventions to support assessment and decision-making for people with dementia living in care homes: A systematic review - Tunnard, India; Gillam, Juliet; Harvey, Catherine; Davies, Nathan; Vickerstaff, Victoria; Ellis-Smith, Clare; Evans, Catherine J. (Frontiers in Dementia, 2022)
Introduction: As dementia progresses, care needs increase leading many to require 24-hour care in care homes. eHealth interventions have the potential to improve care processes of assessment and decision making for people with dementia. However, little is known on the acceptability and effectiveness in care homes. Aim: To identify and explore the components, acceptability and effectiveness of eHealth interventions for people with dementia, families and staff to support assessment and decision-making in care homes. Methods: A mixed methods systematic review using narrative synthesis. Four databases were searched (Embase, PsycINFO, MEDLINE and CINAHL) from 2000-July 2021. Quality appraisal used validated assessment tools appropriate for the study design. Results: Twenty-six studies met eligibility criteria. Study designs and interventions were heterogenous. Overall quality was high to moderate. Interventions that promoted supportive, practical learning through integrated working and provided staff with language to communicate resident symptoms were favoured by staff. We found evidence that indicated that residents were willing to use video consultations, however families preferred face-to-face consultations. Fifteen studies considered effectiveness. Use of eHealth interventions indicates an improvement in resident outcomes in appropriate prescribing and advance care planning. Staff knowledge, confidence and well-being were also improved. Hospitalisations were reduced when a video consultation component was implemented. Discussion: Care home staff require support to meet the often multiple and changing care needs of residents with dementia. eHealth interventions can improve outcomes for staff and residents and facilitate integrated working with external professionals to support assessment and management of care. Further work is required to understand acceptability for residents and their families and effectiveness on family outcomes, particularly in non-Western cultures and high-income countries.